ROLE OF AI DRIVEN BANKING SERVICES IN ENHANCING CUSTOMER EXPERIENCE IN RETAIL BANKING: A MARKET SEGMENTATION APPROACH - Singh, Harpreet; Singh, Sirjan Paul (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Modern internet-based banking has given way to online and mobile banking, leading to a shift in customer expectations and behaviours. Customers now demand more than just basic financial transactions; they seek personalized, convenient, and efficient banking. The adoption of AI in retail banking represents a paradigm shift in the industry’s approach to customer engagement. Traditionally, banks relied on static, one-size-fits-all solutions that could not adequately address the diverse needs and preferences of their customers. This study analyses the customers’ perceptions have been studied for the AI driven banking. The sample size in the study is 250 banking customers. With the help of cluster analysis, it was found that the customers can be segmented in the three major categories namely Service Quality Oriented Customers, Financially Rationale Customers and Cautious Customers. The segments have exclusive perceived benefits and expectations from AI driven banking.